Conservação preventiva na Reserva Técnica Curt Nimuendajú - VICENTE, Bianca Cristina Ribeiro (2019)
The ethnographic object is produced manually by many cultures over time. Inside the museum is the material basis for anthropological and cultural studies, and when went through the scientific process of musealization, they must be preserved. The Museu Paraense Emilio Goeldi safeguard at the Curt Nimuendajú Storage Room a great Ethnography collection of more than 14,000 objects of indigenous, African and regional. This storage room has an alternative acclimatization system that is controlled with the use of supply fans, exhaust fans and dehumidifiers the relative humidity. For the preservation of museum objects, one of the current practices in museums is Preventive Conservation which aims to extend the good physical and chemical conditions of the colletion, acting in preventing the deterioration of agents such as unsuitable temperature and relative humidity. Based on this subject, there was held the monitoring of the environmental conditions of the storage room aiming to analyze the temperature and relative humidity (RH) of the macro environment (room) and micro (cabinets, drawers and containers) for five months. Three dataloggers were programmed to collect every two hours in ten different places in the reserve for the macro environment and twelve to the micro. Also were used a term hygrometer and an infrared thermometer for five days. The macro average temperature was 30,25 °C and RH of 55,90%, with variations of 1,34°C and 5,31%, respectively. The micro environment averaged 29,97°C and 54,82% RH, with variation of 1,28 °C and 4,64%. The averages of relative humidity in both the macro and the micro environment are in accordance with international standards of Preventive Conservation, on the other hand the temperature was very high. However, variations had low values which provides greater stability to parts which suffer minor dimensional changes. However, it should be noted that the Amazon has unique characteristics and that these patterns considered inadequate in the literature may not have the same effect on materials used with the high Amazonian temperatures therefore it is noticed the need to carry out further deeper studies directed at recognition the constituents of the objects to monitor whether they are occurring chemical reactions and in which speeds. There is the importance of thinking Preventive Conservation measures that reflect and respect the climate and museological reality of the region.